Political Knowledge and Its Effect on Voting Decisions: Generation Z Viewers of 'Dirty Vote' Documentary - Yoma Bagus Pamungkas; Yuwanto Yuwanto; Muhammad Adnan; Nurul Hasfi (Jurnal the Messenger, 2025)
Introduction: The 2024 Indonesian presidential election will see significant Generation Z participation, yet unverified political information may affect their understanding. The documentary ‘Dirty Vote’ has the potential to enhance political knowledge and influence voting decisions, particularly regarding election fraud--a key concern for Generation Z voters who are active digitally but vulnerable to misinformation. Using the Elaboration Likelihood Model (ELM), this study examines how the documentary influences political knowledge, mediates voting decisions, and affects political engagement. The research evaluates whether ‘Dirty Vote’ can effectively enhance political understanding and shape voting choices among Generation Z.